The Message : the Bible in contemporary language - Peterson, Eugene H., 1932-2018 (NavPress, published in alliance with Tyndale House Publishers, Incc., 2018)
"'The Message' is a contemporary rendering of the Bible from the original languages, crafted to present its tone, rhythm, events, and ideas in everyday language"--Half-title page.